Analisis Sungai Ijo Gading Sebagai Daya Tarik Wisata di Kabupaten Jembrana, Bali - Anak Agung Ketut Sri Candrawati; Dinar Sukma Pramesti (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2020)
Ijo Gading River is located in a strategic area which cuts across Negara, the capital city of Jembrana Regency, Bali. This river has a great potency to be packed as a tourism destination that can attract tourists to come. To develop the Ijo Gading River as one of tourism destinations, then it is necessary to conduct a research to analyze the internal and external factors possessed by Ijo Ga?ing River as one of tourism destinations at Jembrana, Bali. The results of the research are expected to be considerations for the community, government, and other related parties to develop the potency of Ijo Gading River. This study is a descriptive qualitative research which used observation, interview, literature research, and document study to gain data. The data were analyzed using SWOT analysis which stands for strengths, weaknesses, opportunities, and threats coming from the external factor. The results reveals, from the internal factors, Ijo Gading River possesses some strengths and weaknesses. Its strengths are its historical value, the richness of its culture, and natural landscape which is the traditional fishing boats. Meanwhile its weaknesses are it is not organized well yet, the lack of proper facilities, and the condition of the river that becomes shallower. From the external perspective, Ijo Gading river has several threats and opportunities. The threats are the competitive atmosphere among the same kinds of tourism destinations, its function as a river is destroyed by the activities done around the river, as well as river pollution. But the opportunities are the large empty area, empowering the community, and the community's active participation to develop the tourism activities there. Keyword: Potency, Ijo Gading River, tourism destination